Extracellular alpha‐amylase from halophilic bacteria Marinobacter sp. LES TG5: Isolation, optimization, and characterization - Parwata, I Putu; Julyasih, Ketut Srie Marhaeni (Indonesian Journal of Biotechnology, 2025)
The growing demand for stable and effective enzymes requires the discovery of novel microbial producers. Alpha‐amylase is an enzyme in high demand by various industries; however, the discovery of novel and stable alpha‐amylase producers remains limited. This study aims to isolate, optimize, and characterize extracellular alpha‐amylase from halophilic bacteria Marinobacter sp. LES TG5. Bacteria were isolated from saltwater and soil samples collected from traditional salt ponds in Les Village, Bali, Indonesia. Initial screening on starch agar yielded several amylase‐producing colonies, and subsequent spectrophotometric assays identified one promising isolate (LES TG5), which demonstrated an initial activity of 0.63 U/mL. The production of amylase was significantly enhanced by a multi‐stage optimization process. This involved first identifying optimal carbon and nitrogen sources, followed by a one‐variable‐at‐a‐time approach to determine the ideal nutrient levels, salt concentration, and incubation time. This optimization led to an 11‐fold increase in activity, from 0.63 U/mL to 6.99 U/mL, achieved with a medium containing 2.4% (w/v) nutrient broth, 0.4% (w/v) maltose, and 3% (w/v) NaCl with an incubation time of 22 hours. Enzyme characterization revealed optimal amylase activity at pH 7, 55 °C, and 3% (w/v) NaCl. While Ca2+ and Mg2+ had no effect on amylase activity, Pb2+, Fe2+, Sn2+, and Al3+ significantly reduced it. Importantly, the amylase demonstrated outstanding stability in organic solvents such as methanol, ethanol, and n‐hexane, suggesting its potential as a biocatalyst for chemical synthesis in non‐aqueous systems. Furthermore, its notable stability against surfactants and detergents highlights its promise as an additive in cleaning product formulations.